Sentencing and criminal justice - Ashworth, Andrew (Cambridge : Cambridge University Press, 2015)
Now in its sixth edition, Sentencing and Criminal Justice has been extensively rewritten to reflect recent legislation, guidelines and judicial decisions. New material includes comparative sentencing research, which looks at models from other countries in comparison with the approach in England and Wales, and an additional chapter focusing on civil preventive orders and other ancillary orders. Written with clarity of expression coupled with critical analysis, this textbook offers an unrivalled combination of expertise, accessibility and coverage. This is the essential text for anyone interested in criminal justice.
An introduction to English sentencing -- Sentencing and the constitution -- Sentencing aims, principles and policies -- Elements of proportionality -- Aggravation and mitigation -- Persistence, prevention and prediction -- Equality before the law -- Multiple offenders -- Custodial sentencing -- Non-custodial sentencing -- Ancillary orders and civil preventive orders -- Special sentencing powers -- Procedural issues at sentencing -- Sentencing, guidelines and the punitive state.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Sentences (Criminal procedure) -- Great Britain; Punishment -- Great Britain